PALLIATIVE CARE IN HIGHER EDUCATION INSTITUTIONS: A PROMISING CHALLENGE - Luciana Colares Maia; Alexandre Ernesto Silva; Lorena Caldeira de Melo; Maria Izabel dos Santos; Pâmela Carvalho Pupo (PsychTech & Health Journal)
The new epidemiological profile of the Brazilian population requires changes in the curriculum of Higher Education Institutions concerning the process of training medical professionals. The study aimed to investigate palliative care teaching in Brazilian medical schools. It was guided by the research question: What is the current status of palliative care education in medical schools across Brazil? Searches were carried out in the electronic databases of the Virtual Health Library, using the Descriptors in Health Sciences and Medical Subject Headings: Palliative care; Medical Education and Diseases. As inclusion criteria, English, Portuguese, and Spanish publications were chosen in articles with full-text availability and free access to the searched databases. Results: 55 publications were identified from 2016-2021, of which only 25 documents met the inclusion criteria. The topic of palliative care emerges as an educational incentive capable of promoting essential and surprising discussions throughout graduation and providing educational strategies that can provide opportunities for improving skills and competencies based on integral models centered on the person. This requires a demand for training in this subject as a multidisciplinary approach that prepares the team to deal with patients with life-threatening incurable chronic diseases and infinitude.